ANALISA CONTRIBUTION MARGIN TERHADAPPERENCANAAN PENJUALAN PRODUK PADA TOKO ROTI BEKASI - Baginda Cristian L. Siburian; Dea Alfianti; Ira Fitriani; Sazkya Renata L. Siregar (Samudra Publisher, 2024)
This study aims to analyze the break-even point of a company using a contribution margin approach to determine the required sales volume to achieve the target profit. The research method used in this study is quantitative. The scope includes collecting data from income statements, covering aspects such as selling price per unit, variable costs, contribution margin, and sales composition. This data is analyzed by calculating the contribution margin per unit and total sales, which are then subtracted by fixed costs to calculate net income. This analysis applies the contribution margin formula and the contribution margin ratio to calculate the level of operational activity needed to achieve the profit target or break-even point. The results of this study are expected to provide guidance for the company in sales planning and strategic decision-making related to cost and profit management.